2019
DOI: 10.1002/mbo3.772
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and proteomic acclimation of Staphylococcus aureus when incubated in a defined minimal medium supplemented with 5% sodium chloride

Abstract: Staphylococcus aureus is a versatile bacterium that can adapt to survive and grow in a wide range of salt concentrations. This study investigated whether the cells could mount a response to survive a challenge of 5% NaCl in a minimal incubation medium that would not support cell replication. Cells were grown in liquid culture, washed and then incubated for 90 min at 37°C in a medium that contained only glycine and glucose as substrates in PBS plus trace elements. The control cells were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…This was proposed as an adaptive mechanism by the bacteria to utilize amino acids for energy and alternative resources to support growth based on nutrient availabilities from the surrounding environment (Zhu et al, 2007;Stipetic et al, 2016). To date, the studies have demonstrated that the exposure of S. aureus to subtle variations in temperature, pH and NaCl resulted in significant alterations in cytoplasmic amino acids, proteins and external morphological structures compared with bacterial cells grown under normal conditions (Crompton et al, 2014;Wehrli et al, 2014;Alreshidi et al, 2015;Alreshidi et al, 2016;Alreshidi et al, 2019). It has also been shown that S. aureus consumed a significant amount of glycine when incubated in minimal media supplemented with 5% NaCl compared to the cells grown in normal conditions (Alreshidi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This was proposed as an adaptive mechanism by the bacteria to utilize amino acids for energy and alternative resources to support growth based on nutrient availabilities from the surrounding environment (Zhu et al, 2007;Stipetic et al, 2016). To date, the studies have demonstrated that the exposure of S. aureus to subtle variations in temperature, pH and NaCl resulted in significant alterations in cytoplasmic amino acids, proteins and external morphological structures compared with bacterial cells grown under normal conditions (Crompton et al, 2014;Wehrli et al, 2014;Alreshidi et al, 2015;Alreshidi et al, 2016;Alreshidi et al, 2019). It has also been shown that S. aureus consumed a significant amount of glycine when incubated in minimal media supplemented with 5% NaCl compared to the cells grown in normal conditions (Alreshidi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Modifications to the metabolic pathways are related to decreasing cell size, although many different pathways were detected using the RNA−seq analysis here. The reduction in growth and regulation of the basal metabolic activity of cells represent adaptation responses and survival strategies, along with other metabolic changes, to reduce the harmful effects of antimicrobials [63,65,67].…”
Section: Rna−sequencing Results and Phenotypic Properties Of These Smentioning
confidence: 99%
“…Modifications to the amino-acid profile influence many biological pathways in cells, as amino acids are required for protein synthesis, and used for synthesis of the cell-wall and nucleic acids, and they can be used as energy substrates [64]. Reductions in cytoplasmic amino acids has been associated with slower rates of metabolism, to conserve energy for basal metabolism [65]. Modifications to cell membranes and the cell wall are known to be important to maintain cellular homeostasis, by the protection of cells from changes in the environment.…”
Section: Response Mechanisms To Ddac Of the Ddac-tolerant S Epidermimentioning
confidence: 99%
“…aureus used in the current study was isolated from patients who were suffering from chronic muscle pain 14 . This bacterium was used in following investigations to study metabolic and proteomic adaptation to alterations in the environmental factors 5,6,9 .…”
Section: S Aureus Strain and Growth Conditionsmentioning
confidence: 99%
“…When S. aureus was grown under sub-optimal conditions, significant changes in the cytoplasmic amino acid, fatty acid and protein patterns were observed 6,8 . Thus, it was assumed that characteristic and specific changes in the amino acid and fatty acid metabolites as well as protein composition led to the survival of S. aureus when exposed to confined nutrition in combination with higher concentrations of NaCl 9 . A recent study indicated that hydrogen peroxide (H 2 O 2 ) combined with various temperatures and pH induced alterations in the amino acid profiles of clinical isolate of S. aureus 10 .…”
Section: Introductionmentioning
confidence: 99%